2017
DOI: 10.1111/apha.12896
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles of healthy origins improve endothelial progenitor cell dysfunction via microRNA transfer in an atherosclerotic hamster model

Abstract: The data reveal that late EPCs from atherosclerotic model exhibit distinctive features and are dysfunctional, and their function recovery can be supported by MP ability to transfer miRNAs. These findings bring a new light on the vascular repair in atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 81 publications
2
51
0
Order By: Relevance
“…The original idea of EV transfer of miRNAs began in 2007 when a seminal study by Valadi et al proved exosomes to contain functional miRNAs, which can be delivered to another cell . In addition, many studies have reported that functional miRNAs transferred by MVs mediate cell‐cell communication . Intercellular communication processes based on extracellular miRNAs can be considered as consisting of 3 key steps: (a) miRNAs are secreted from cells and selectively packaged into appropriate carriers.…”
Section: Mirnas Are Found In Mvs and Transferred Between Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original idea of EV transfer of miRNAs began in 2007 when a seminal study by Valadi et al proved exosomes to contain functional miRNAs, which can be delivered to another cell . In addition, many studies have reported that functional miRNAs transferred by MVs mediate cell‐cell communication . Intercellular communication processes based on extracellular miRNAs can be considered as consisting of 3 key steps: (a) miRNAs are secreted from cells and selectively packaged into appropriate carriers.…”
Section: Mirnas Are Found In Mvs and Transferred Between Cellsmentioning
confidence: 99%
“…On the other hand, MVs and the miRNAs they contain have inspired many studies on pathology and disease resistance . For a long time, it has been thought that the therapeutic effect of MV‐delivered miRNAs is obviously superior to that of traditional treatment.…”
Section: Existing Problems Of Mvs and The Clinical Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that late EPCs obtained from an experimental model of atherosclerosis have altered morphological and functional characteristics, and altered immunophenotypic profile and lower levels of miRNAs involved in vascular repair processes (miR‐10a; miR‐21; miR‐126; miR‐146a; miR‐223). Moreover, MPs of healthy animals improve atherosclerosis‐associated late EPC dysfunction by their ability to transfer these miRNAs and to stimulate IGF‐1 expression …”
mentioning
confidence: 99%
“…In the peripheral blood, EPCs undergo a maturation process from an early to a late phenotype, which can be evaluated by cytofluorimetric analysis by the immunophenotype change. Possible dysfunctional moments of this complex repair system could be schematized in: decreased mobilization of EPCs from the bone marrow, decreased homing capacity of late EPCs, lower ability to modulate positively the function of late EPCs by MPs (Fig. ).…”
mentioning
confidence: 99%